Feline upper respiratory tract disease: feline herpesvirus-1 - Sodarat, Chollada (Veterinary Integrative Sciences, 2014)
Feline herpesvirus-1 (FHV-1) is recognized as one of the most important pathogens of feline upper respiratory tract infections with clinical sign of conjunctivitis and keratitis. After the initial infection, cats are unable to eliminate the virus and develop a carrier state, with intermittent episodes of virus shedding. This article discusses pathogenesis, clinical signs, diagnosis, treatment and prevention of disease caused by FHV-1 infection.